Unintentional child poisoning risk: A review of causal factors and prevention studies. Issue 2 (3rd April 2017) - Schwebel, David C.; Evans, W. Douglas; Hoeffler, Stephen E.; Marlenga, Barbara L.; Nguyen, Simone P.; Jovanov, Emil; Meltzer, David O.; Sheares, Beverley J.
ABSTRACT: Unintentional child poisoning represents a significant public health priority in the United States and globally. This article was written to accomplish three goals: (a) outline and discuss a conceptual model of factors that lead to unintentional poisoning incidents among children under 5 years of age, including the roles of individual people, the environment, packaging and labeling of toxic products, and community and society; (b) review published literature concerning interventions designed specifically to reduce unintentional child poisoning; and (c) draw conclusions about what is known and what gaps exist in the current literature on unintentional child poisoning prevention to inform development, evaluation, and implementation of empirically supported, theoretically based prevention programs. The need for multi-faceted, multi-disciplinary, team-based approaches to prevention is emphasized.